Fantasies of the Good Life: Responding to Rape Culture in 13 Reasons Why. Issue 1 (1st March 2021) - Greensmith, Cameron; Froese, Jocelyn Sakal
Abstract: Using Lauren Berlant's concept of cruel optimism, we address the ways in which rape culture, as depicted in Jay Asher's 13 Reasons Why and the first two seasons of the Netflix adaptation, shapes girls' agency and attachment to possible futures. We take seriously the ways in which social and institutional structures in 13 Reasons Why produce girls' livability as tied to everyday forms of sexist violence, which supposedly grant them access to what they think of as the good life. Bound up in these cruel attachments is a more limited set of options than may appear available: girls are called upon to endure daily violence in hopes of achieving this fantasy or to choose alternative paths, such as slow death or even suicide.